Dividing the Nile : Egypt's economic nationalists in the Sudan, 1918-56 - Mills, David E. (David Eugene) (Cairo ; New York : The American University in Cairo Press, 2014)
Most scholarship has attributed Sudanese independence in 1956 to British dominance of the Condominium, historical animosity toward Egypt, or the emergence of Sudanese nationalism. Dividing the Nile counters that Egyptian entrepreneurs failed to develop a united economy or shared economic interests, guaranteeing Egypt's 'loss' of the Sudan.--Provided by publisher
The 'natural' unity of the Nile Valley -- 'Successful' division of water resources -- Agreement, institutions, and opportunities, 1936-1939 -- A valley divided : transportation difficulties -- Disguised exploitation : agricultural and industrial designs on the Sudan -- An expanded Sudanese market? : Egyptian exports to the Sudan -- An economic lifeline? : Egyptian reliance on Sudanese imports.
Includes bibliographical references (pages 277-353) and index.
Keywords: 1899 - 1999; Nationalism -- Sudan -- History -- 20th century; Nationalism -- Egypt -- History -- 20th century; Economic history; Nationalism; Sudan -- History -- 1899-1956.; Sudan -- Economic conditions -- 20th century; Egypt -- History -- 1919-1952.; Egypt -- Economic conditions -- 1919-1952.; Egypt; Sudan; History